Penggunaan Instrumen dalam Layanan Bimbingan dan Konseling Sekolah - Adinda Siti; Ainun Fadillah; Annisa Zahra; Maharani Maharani; Siti Husna; Vania Azarine (Lembaga Pengembangan Kinerja Dosen, 2024)
Instrumentation applications, which consist of tests and non-tests, are important tools used by guidance and counseling teachers to collect accurate data about students, which is then used to provide appropriate guidance. This research aims to explore the use of instrumentation applications in Guidance and Counseling (BK) services at schools. The method used in this research is a literature approach, collecting data from various scientific publications that are relevant to the research topic. The research results show that although instrumentation applications are very important in understanding students' needs and problems, many guidance and counseling teachers still face obstacles in their use, mainly due to a lack of understanding and adequate training. Important stages in implementing instrumentation applications include collection, planning, reporting, evaluation and follow-up. To provide effective guidance and counseling services, guidance and counseling teachers need to understand and be proficient in the use of instrumentation applications, which will help students realize their potential and solve the problems they face.